2012
DOI: 10.1017/s0007114512001821
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and CHD: the Greek European Prospective Investigation into Cancer and Nutrition cohort

Abstract: Adherence to the Mediterranean diet (MD) has been reported to improve CHD prognosis and to be inversely associated with CHD mortality. The aim of the present study was to investigate the association of adherence to the MD with CHD incidence and mortality in the Greek European Prospective Investigation into Cancer and Nutrition cohort, a population with traditional Mediterranean roots. In a general population sample of 23 929 adult men and women with no CVD or cancer at enrolment, a validated FFQ was interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 37 publications
4
107
0
2
Order By: Relevance
“…A possible explanation for such difference between men and women may rely on the fact that men were generally more likely to be smokers and drink more alcohol (18,20,25) , thus somehow counteracting the potential beneficial effects of legumes. Another methodological issue may depend on lower accuracy in reporting dietary patterns among men than women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for such difference between men and women may rely on the fact that men were generally more likely to be smokers and drink more alcohol (18,20,25) , thus somehow counteracting the potential beneficial effects of legumes. Another methodological issue may depend on lower accuracy in reporting dietary patterns among men than women.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the lack of significant results in meta-analyses of studies conducted in Mediterranean countries could be the impact on cardiovascular health of all components of the diet typically consumed in these countries, or at least those included in the individual analyses. (17) Bernstein et al (2010) (23) , F Buckland et al (2009) (20) , M Kelemen et al (2005) (18) , F Kokubo et al (2007) (19) , M Buckland et al (2009) (20) , F Kokubo et al (2007) (19) , F Martinez-Gonzalez et al (2011) (24) Nagura et al (2009) (22) Dilis et al (2012) (25) , F Dilis et al (2012) (25) , M Haring et al (2014) (23) Total ( (19) , M Mizrahi et al (2009) (21) Misirili et al (2012) (27) Haring et al (2015) (29) Total ( (24) Bazzano et al (2001) (17) Kokubo et al (2007) (19) , F Kokubo et al (2007) (19) , M Nouri et al (2016) (30) Nagura et al (2009) (22) Total ( The study-specific RR and 95 % CI are represented by the black square and horizontal line, respectively; the area of the black square is proportional ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, several indices of MD patterns as well as adherence to the DASH diet and other healthy diet scores are associated with a lower risk of stroke, CHD and CVD in numerous prospective cohort studies in different populations (69,(80)(81)(82)(83)(84) , residual confounding by other lifestyle and socioeconomic factors remains a major challenge in determining causality. While a trial of the DASH diet has demonstrated that adherence to DASH can reduce numerous cardiovascular risk factors (85) the causal effects on mortality and on other age-related end points are unknown.…”
Section: From Observation To Intervention?mentioning
confidence: 99%
“…It starts during the intrauterine environment that influences health outcome at adult age, as low birth weight is associated with an increased risk of diseases [2]. Epidemiological studies have clearly established that a lifelong healthy lifestyle, composed of moderate but regular physical exercise (EX) and a balanced diet, prolongs lifespan and reduces the odds of developing cardiovascular diseases (CVD) [10,16,45,46,59,76]. The detrimental effects of the so-called Western diet (WD) and lifestyle on the cardiovascular system have, therefore, been established by numerous studies showing the contribution of physical inactivity (PI) and poor-quality/high-calorie intake on the development of obesity, hypertension, diabetes, and CVD [9,37].…”
Section: Introductionmentioning
confidence: 99%